O universo numa casca de marisco : arqueologia animista aplicada aos sambaquis e zoomorfos do Brasil meridional - Pompeu, Filipi Gomes de (2021)
This work is an attempt to interpret and foster a symbolic vision of the sites of southern Brazil's conchiferous matrix (sambaquis and concheiros) and the typical style sculptures associated with this type of site: the zoomorphs. For that, we endeavor to elaborate and describe a detailed theoretical matrix pertinent to this multinatural perspective and analogous to the construction of sambaquis - perspectivist animism, ontology, ontography and phenomenology occupy an important part of our idea. Based on the local example of the sambaquis and ceramic shells from Babitonga Bay, Santa Catarina, we were able to establish an overview of the theoretical and practical motivations of these populations regarding the cosmos they share with the most distinct animal forms. With this, we hope to have contributed and sediment a new way of studying and thinking about this archaeological site so important for the history of Brazilian archaeology.